2016
DOI: 10.1016/j.neuropsychologia.2016.09.023
|View full text |Cite
|
Sign up to set email alerts
|

What's the gist? The influence of schemas on the neural correlates underlying true and false memories

Abstract: The current study used a novel scene paradigm to investigate the role of encoding schemas on memory. Specifically, the study examined the influence of a strong encoding schema on retrieval of both schematic and non-schematic information, as well as false memories for information associated with the schema. Additionally, the separate roles of recollection and familiarity in both veridical and false memory retrieval were examined. The study identified several novel results. First, while many common neural region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 99 publications
(198 reference statements)
5
50
2
Order By: Relevance
“…The aHPC has been suggested to be more involved in global or gist‐like processing (e.g., Poppenk et al, ; Robin & Moscovitch, ), and our results provided supports for the role of the aHPC in schema‐related memory retrieval. Consistent with our results, Webb et al () investigated subsequent memory effects for objects that were encoded either in congruent or incongruent scenes and found increased aHPC activation for schema‐related recollection. Human fMRI studies have also suggested that activation in the aHPC is associated with constructing mental representations of scenes (Dalton, Zeidman, McCormick, & Maguire, ; Zeidman & Maguire, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The aHPC has been suggested to be more involved in global or gist‐like processing (e.g., Poppenk et al, ; Robin & Moscovitch, ), and our results provided supports for the role of the aHPC in schema‐related memory retrieval. Consistent with our results, Webb et al () investigated subsequent memory effects for objects that were encoded either in congruent or incongruent scenes and found increased aHPC activation for schema‐related recollection. Human fMRI studies have also suggested that activation in the aHPC is associated with constructing mental representations of scenes (Dalton, Zeidman, McCormick, & Maguire, ; Zeidman & Maguire, ).…”
Section: Discussionsupporting
confidence: 92%
“…The aHPC has been suggested to be more involved in global or gist-like processing (e.g., Poppenk et al, 2013;Robin & Moscovitch, 2017), and our results provided supports for the role of the aHPC in schema-related memory retrieval. Consistent with our results, Webb et al (2016) investigated subsequent memory effects for objects that were encoded either in congruent or incongruent scenes and found increased aHPC activation for schema-related recollection.…”
Section: Hippocampus In Schema-related Memory Retrievalsupporting
confidence: 88%
See 3 more Smart Citations